Antibodies in children with malaria to PfEMP1, RIFIN and SURFIN expressed at the Plasmodium falciparum parasitized red blood cell surface - Maria Del Pilar Quintana (2019)
© 2018 The Author(s). Naturally acquired antibodies to proteins expressed on the Plasmodium falciparum parasitized red blood cell (pRBC) surface steer the course of a malaria infection by reducing sequestration and stimulating phagocytosis of pRBC. Here we have studied a selection of proteins representing three different parasite gene families employing a well-characterized parasite with a severe malaria phenotype (FCR3S1.2). The presence of naturally acquired antibodies, impact on rosetting rate, surface reactivity and opsonization for phagocytosis in relation to different blood groups of the ABO system were assessed in a set of sera from children with mild or complicated malaria from an endemic area. We show that the naturally acquired immune responses, developed during malaria natural infection, have limited access to the pRBCs inside a blood group A rosette. The data also indicate that SURFIN4.2 may have a function at the pRBC surface, particularly during rosette formation, this role however needs to be further validated. Our results also indicate epitopes differentially recognized by rosette-disrupting antibodies on a peptide array. Antibodies towards parasite-derived proteins such as PfEMP1, RIFIN and SURFIN in combination with host factors, essentially the ABO blood group of a malaria patient, are suggested to determine the outcome of a malaria infection.